The stigma and prejudice of leprosy: influence on the human condition - Saliba Garbin, Clea Adas [UNESP]; Isper Garbin, Artenio Jose [UNESP]; Oliveira Gomes Carloni, Maria Emilia [UNESP]; Saliba Rovida, Tania Adas [UNESP]; Martins, Ronald Jefferson [UNESP] (Soc Brasileira Medicina Tropical, 2015)
Introduction: To analyze the knowledge, feelings and perceptions involving patients affected by leprosy, as a better understanding of these factors may be useful to decrease the stigma and prejudice associated with the condition. Methods: The study cohort consisted of 94 patients who underwent treatment for leprosy at the Health Units in the City of Cuiaba, Mato Grosso (MT), Brazil. The study questionnaire included items to collect information on socio-demographic data, knowledge about the disease, stigma, prejudice, self-esteem and quality of life of leprosy patients. Bivariate analyses were used to assess the data based on the chi-square test with a 5% significance threshold. Results: The results revealed that the study population consisted predominantly of males (55.3%) with an income between 1 and 3 times the minimum wage (67%). The survey respondents reported that the most significant difficulties related to the treatment were the side effects (44.7%) and the duration of the treatment (28.7%). A total of 72.3% of the subjects were knowledgeable about the disease, of whom 26.6% had the leprosy reaction. Stigma and prejudice were cited by 93.6% of the participants. Based on the responses, 40.4% of patients reported being depressed and sad, and 69.1% of the subjects encountered problems at work after being diagnosed. A total of 45.7% of the patients rated their quality of life between bad and very bad. Conclusions: Our results suggest that leprosy causes suffering in patients beyond pain and discomfort and greatly influences social participation.
Keywords: Leprosy; Prejudice; Social stigma; Social discrimination